Cachexia induced by cancer and chemotherapy yield distinct perturbations to energy metabolism. Issue 1 (24th January 2019) - Pin, Fabrizio; Barreto, Rafael; Couch, Marion E.; Bonetto, Andrea; O'Connell, Thomas M.
Abstract: Background: Cancer cachexia is a metabolic disorder involving perturbed energy balance and altered mitochondrial function. Chemotherapy is a primary treatment option for many types of cancer, but there is substantial evidence that some chemotherapeutic agents can also lead to the development and progression of cachexia. In this study, we apply a comprehensive and systems level metabolomics approach to characterize the metabolic perturbations in murine models of cancer‐induced and chemotherapy‐induced cachexia. Knowledge of the unique pathways through which cancer and chemotherapy drive cachexia is necessary in order to develop effective treatments. Methods: The murine Colon26 (C26) adenocarcinoma xenograft model was used to study the metabolic derangements associated with cancer‐induced cachexia. In vivo administration of Folfiri (5‐fluorouracil, irinotecan, and leucovorin) was used to model chemotherapy‐induced cachexia. Comprehensive metabolic profiling was carried out using both nuclear magnetic resonance‐based and mass spectrometry‐based platforms. Analyses included plasma, muscle, and liver tissue to provide a systems level profiling. Results: The study involved four groups of CD2F1 male mice ( n = 4–5), including vehicle treated (V), C26 tumour hosts (CC), Folfiri treated (F), and C26 tumour hosts treated with Folfiri (CCF). Significant weight loss including skeletal muscle was observed for each of the experimental groups with the tumour hosts showing the most dramatic change (−3.74 g vs. initial body weight in the CC group). Skeletal muscle loss was evident in all experimental groups compared with V, with the CCF combination resulting in the most severe depletion of quadriceps mass (−38% vs. V; P < 0.001). All experimental groups were characterized by an increased systemic glucose demand as evidenced by decreased levels of circulating glucose (−47% in CC vs. V; P < 0.001) and depletion of liver glucose (−51% in CC vs. V; P < 0.001) and glycogen (−74% in CC vs. V; P < 0.001). The cancer‐induced and chemotherapy‐induced cachexia models displayed unique alterations in flux through the tricarboxylic acid cycle and β‐oxidation pathways. Cancer‐induced cachexia was uniquely characterized by a dramatic elevation in low‐density lipoprotein particles (+6.9‐fold vs. V; P < 0.001) and a significant increase in the inflammatory marker, GlycA (+33% vs. V; P < 0.001). Conclusions: The results of this study demonstrated for the first time that cancer‐induced and chemotherapy‐induced cachexia is characterized by a number of distinct metabolic derangements. Effective therapeutic interventions for cancer‐induced and chemotherapy‐induced cachexia must take into account the specific metabolic defects imposed by the pathological or pharmacological drivers of cachexia.